The Effects of Nordic hamstring exercise on the different surface to muscle strength, proprioception and postural sway in healthy adult - Bong , Eun-Bi; Jung , Hyun-Ji; Jung , Hyun-Ji; Jeon, Jeong woo; Hong , Ji-Heon; Yu , Jae-Ho; Kim , Jin- Seop; Lee, Dong-Yeop (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The purpose of this study is to investigate the changes of postural sway and eccentric muscle strength and proprioception on an unstable surface during the Nordic Hamstring Exercise (NHE). Methods/Statistical analysis: Forty male adults participated in this study. All subjects are randomized into groups of stable and unstable surfaces. NHE is administered three times a week for four weeks, with two measurements of muscle strength, proprioception, and postural sway before and after exercise. Paired t-tests were used to compare the differences before and after intervention in the group, and independent t-tests were used to compare the difference of effects between groups. Findings: As a result of this study, there was a significant difference in the joint position sense of knee and hip in the comparison between groups(p<.05). However, there was no significant difference in muscle strength and postural sway. In the comparison between the groups, the joint position sense of knee and hip was not significantly different in the control group, but in the experimental group. There were also significant differences in muscle strength in both the control and experimental groups, and postural sway was significant only in the experimental group. Improvements/Applications: Considering these findings, this study may help to design a more effective exercise for athlete and elderly people